Indigenous bodies and the double face of bare life - Nascimento, Daniel Arruda (Sofia, 2024)
With a step that goes beyond Giorgio Agamben’s primary intention in configuring the concept of bare life, this investigation seeks to inquire if it would be possible to see its potentialities. Some clues left by the philosopher throughout his work could help us in this conversion process. One of them alludes to the Franciscan model of a life outside the law in Altissima povertà, which is still a life that pretends to be naked, just as it seems to be associated with some experience of the Amerindian peoples. In relation to the bodies of the original peoples of our country, a first meaning of their bare life is that it is a precarious life: the people of the forest are, in our violent legal reality, the ones most exposed to death. In a second sense, however, more in tune with the idea of ​​thinking about another bare life, indigenous nudity philosophically considered would have something to teach us.